Determinants of Contemporary Economic Development - Noga, Beniamin (Determinanty współczesnego rozwoju gospodarczego, 2009)
Contemporary economic development is not only a function of classic factors of development, such as land, labour and capital, but also (and above all) the so-called new factors of development, such as intellectual capital, knowledge, education, technology spillover, as well as formal and legal systems on national level, institution (in terms of procedures of behaviour), cultural determinants, and so forth. The article presents the influence of "new" factors on economic development with particular attention paid to the role of work, culture and institution understood as rules of conduct in economic development.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 81, s. 84-92
Keywords: economic development; determinants fo economic development; cultural determinants; institutions